Contracaecum osculatum Rudolphi 1802, s.l. - Hernández-Orts, Jesús S.; Viola, M. Natalia Paso; García, Néstor A.; Crespo, Enrique A.; González, Raúl; García-Varela, Martín; Kuchta, Roman (Zenodo, 2015)
Contracaecum osculatum (Rudolphi, 1802) s.l. Host: Mirounga leonina (Linnaeus) Site in host: stomach Locality: Península Valdés, Chubut province References: Mattiucci et al . (2003) Published as part of Hernández-Orts, Jesús S., Viola, M. Natalia Paso, García, Néstor A., Crespo, Enrique A., González, Raúl, García-Varela, Martín & Kuchta, Roman, 2015, A checklist of the helminth parasites of marine mammals from Argentina, pp. 301-334 in Zootaxa 3936 (3) on page 311, DOI:10.11646/zootaxa.3936.3.1, http://zenodo.org/record/236696